KEBERADAAN ANILIN DI SUNGAI CITARUM HULU AKIBAT PENGGUNAAN AZO DYES PADA INDUSTRI TEKSTIL - Suhendra, Edward; Purwanto, Purwanto; Kardena, Edwan (METANA, 2013)
Abstract The dyeing and printing processes in textile industry produces wastewater containing residual dyes. The most widely used textile dyes are azo dyes. The textile industry is one of the main industries in West Java province, where one of the textile industry centers is Majalaya textile industry center. Majalaya textile industry center had begun since the 1910s, where in Majalaya subdistrict located the most textile companies which produced textile wastewater. Textile wastewater which contained azo dyes discharged into the Citarum Hulu River directly or after treatment in the Waste Water Treatment Plant (WWTP) owned by the company. One of the product metabolites produced from azo dyes biodegradation by bacteria in anaerobic conditions are various anilines. Several anilines which are persistent, could flow to downstream of Citarum Hulu River. Various anilines, referred to as total anilines, could be analyzed by the colorimetric method using visual spectrophotometer. Total anilines in water samples after biodegradation by anaerobic bacteria was 14.46 mg/l highest. While total aniline in river water samples was 3.58 mg/l highest. And at the downstream of Citarum Hulu River, there was total of aniline 1,825 mg/l highest in the river sediment samples. DO in the river water samples were 4.25 - 7.8 mg/l, while pH of the river water samples were 7.1 - 10.7. The occurence of total aniline in textile wastewater and river water samples in Citarum Hulu River (Majalaya subdistrict) and in river sediments at the downstream of Citarum Hulu indicated biodegradation of azo dyes from textile wastewater by anaerobic bacteria. Key words : Citarum Hulu River, textile wastewater, azo dyes, total aniline